NEW NANOSTRUCTURAL CATALYSTS FOR NEUTRALIZATION OF TOXIC GASES IN INDUSTRY - B.Kh. Khussain,; M.Zh. Zhurinov,; A.Z. Abilmagzhanov,; A.S. Sass,; B.B. Teltaye, (Academic Scientific Journal of Chemistry, 2020)
One of the key environmental problems is the protection of the air basin in the cities and industrial zones of the Republic of Kazakhstan. The environmental situation is increasingly affecting the economic well-being of the state, and becoming the most significant factor in the development of the country. The catalytic methods for cleaning exhaust gases from harmful components are a great help in solving these problems. The main advantage of the catalysts is their autonomy, ease of use and accessibility to users. The main indicators of catalysts include such parameters as activity, productivity, resistance to poisons, price, etc. This article shows the presence of active in the complete oxidation reaction of alumina nanoclusters formed during sorption from aqueous solutions of chloroplatinic acid and provides the technological scheme for the production of industrial catalysts